The Effect of Varying Collimator Angles on VMAT planning of Prostate Cancer - Hashir Saeed, Sadiqullah, Hina Manzoor, Hafiz Khush Naseeb Ahmad, Sunnia Shafiq, Qadeer Ahmed, Abdul Basit, Awais Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The variation in collimator angles in the Volumetric Modulated Arc Therapy (VMAT) has been a factor of consideration in modern radiotherapy techniques for the treatment of cancer. Aim: To investigate dose-volume evaluation in planning target volume (PTV) and organs-at-risk (OARs) in prostate carcinoma patients planned with 1.5 arcs for different collimator angles. Methods: The collimator angle plays a vital role in VMAT planning due to leakage of radiation from the leaves of multi-leaf collimator (MLCs). Using the same optimization parameters on designated treatment planning system (TPS), the arcs of VMAT plans were optimized with 0°, 10°, 20°, 30°, 45°, and 90°, and 0°, 350°, 340°, 330°, 315° and 270° collimator angles. Different parameters like homogeneity index (HI), conformity index (CI), gradient index (GI), monitoring units (MUs), low dose coverage (V40Gy), maximum dose (Dmax), mean dose (Dmean), dose-volume histogram (DVH), D98%, D95%, etc. were calculated with Anisotropic Analytical Algorithm (AAA) Version 15.6.04 and results were analyzed. Results: It was found that at 20°, 30° and 45° collimator angles, the dose conformity, homogeneity, and MUs have optimal values. The target coverage and dose to organ at risks at all angles is not significantly affected by different collimator angles. Conclusion: According to this study it is advised to clinical medical physicists to make a solid decision about the collimator angles for treatment. The dosimetric analysis shows that the optimal collimator angle is necessary for different plan analyzing parameters like better conformity and homogeneity. Keywords: Volumetric Modulated Arc Therapy. Prostate cancer, Planning Target Volume, organs-at-risk